Nitrate and ammonia as nitrogen sources for deep subsurface microorganisms - Kutvonen, Heini; Rajala, Pauliina; Carpén, Leena; Bomberg, Malin (Frontiers in Microbiology, 2015)
We investigated the N-utilizing bacterial community in anoxic brackish groundwater of the low and intermediate level nuclear waste repository cave in Olkiluoto, Finland, at 100 m depth using 15N-based stable isotope probing (SIP) and enrichment with 14∕15N-ammonium or 14∕15N-nitrate complemented with methane. Twenty-eight days of incubation at 12°C increased the concentration of bacterial 16S rRNA and nitrate reductase (narG) gene copies in the substrate amended microcosms simultaneously with a radical drop in the overall bacterial diversity and OTU richness. Hydrogenophaga/Malikia were enriched in all substrate amended microcosms and Methylobacter in the ammonium and ammonium+methane supplemented microcosms. Sulfuricurvum was especially abundant in the nitrate+methane treatment and the unamended incubation control. Membrane-bound nitrate reductase genes (narG) from Polarimonas sp. were detected in the original groundwater, while Burkholderia, Methylibium, and Pseudomonas narG genes were enriched due to substrate supplements. Identified amoA genes belonged to Nitrosomonas sp. 15N-SIP revealed that Burkholderiales and Rhizobiales clades belonging to the minority groups in the original groundwater used 15N from ammonium and nitrate as N source indicating an important ecological function of these bacteria, despite their low number, in the groundwater N cycle in Olkiluoto bedrock system.